Global Financial Stability Report, October 2009 : Navigating the Financial Challenges Ahead. (Global Financial Stability Report; Global Financial Stability Report, 2009)
The October 2009 Global Financial Stability Report chronicles the evolution of the path toward reestablishing sound credit intermediation and the near-term risks that could interrupt its restoration, including the rising burden of sovereign financing. The report addresses how to restart securitization markets and the pitfalls if done improperly. The effectiveness of unconventional public sector interventions and the principles for disengagement are discussed. The report also discusses the design of medium-term policies that aim to reshape the financial system to make it more resilient and stable.